Factors determining uptake of diabetic retinopathy screening in Oxfordshire. Issue 7 (10th April 2017) - Moreton, R. B. R.; Stratton, I. M.; Chave, S. J.; Lipinski, H.; Scanlon, P. H.
Abstract: Aims: To investigate variables at the demographic and primary care practice levels that influence the uptake of diabetic retinopathy screening. Methods: Data were extracted from the management software of one screening programme for 21 797 people registered with 79 general practices. Uptake was examined by gender, age group, modality of screening (mobile unit at general practice versus high‐street optometrist), and by general practice. A telephone survey of high‐street optometrists provided information on the availability of screening appointments. Results: Uptake was 82.4% during the study period, and was higher for men (83.2%) than for women (81.5%) ( P = 0.001). Uptake varied by age group ( P < 0.001), being lowest in those aged 12–39 years (67%). Uptake was higher for people invited to a general practice for screening by a mobile unit (83.5%) than for those invited for screening by a high‐street optometrist (82%) ( P = 0.006). After adjusting for these factors and for socio‐economic deprivation score at the location of the general practice, heterogeneity in uptake rate was still observed between some practices. Our survey of optometrists indicated wide variation in the availability of time slots for screening during the week and of screening appointment provision. Conclusions: Diabetic retinopathy screening services do not achieve high uptake among the youngest or oldest age groups. Practices in the least deprived areas had the highest uptake. Variation in uptake between general practices after adjustment for individual‐level variables and deprivation suggests that practice‐level factors may have an important role in determining rates of screening attendance.